Novel CT Features of an Abdominal Gossypiboma in a Female Dog - Mylene Auger; Shelly Olin; Federica Morandi (Case Reports in Veterinary Medicine)
Case Description. An eight-year-old Golden Retriever was presented with hypercalcemia and a complex abdominal mass. Clinical Findings. A well-defined, heterogeneously contrast-enhancing, cavitary, soft tissue attenuating, non-organ associated abdominal mass was identified caudal to the right kidney. This mass was confluent with the distal tip of the right limb of the pancreas. A connected large, rim enhancing, cystic subcutaneous mass was also present in the right lumbar subcutaneous tissues, and there were multiple fistulous tracts through the hypaxial musculature. Treatment and Outcome. The dog underwent a surgical exploratory laparotomy and a gossypiboma was removed from the intra-abdominal mass; the cystic extra-abdominal mass was drained percutaneously. Surgical recovery was uneventful and a follow-up CT after 3 months was consistent with resolving granulomatous inflammation and fibrosis. Clinical Relevance. The presence of multiple peripherally enhancing tracts extending from the abdominal mass through the hypaxial musculature is a CT feature which has not yet been described in the veterinary literature. Additionally, incorporation of the pancreas into the abdominal mass has also not yet been described in the veterinary literature.